ISLAM DAN NEO-MODERNISME/ POST-MODERNISME: Perspektif Nurcholish Madjid dan Abdurrahman Wahid - Yuyun Rohmawati (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2021)
The Western has always insulted Islam as an out of date, irrational, dogmatic, mystical, static, undemocratic religion and so on. Despite the fact, Islam is a religion that rahmatan lil ‘alamin, dynamic and democratic. But the Western negative assessment of Islam is very strongly attached to their memory. So it’s quite difficult to change the Western understanding of Islam. Furthermore, Islamic societies who are too fanatical tend to shut down and reject the modern era. That is what make the problem more complex. Therefore, Indonesian Muslim Intellectuals sought to overcome this problem by developing Neo-modernism/ Post-modernism (in the 20th century). This is in accordance with the purpose of this article which is to find out Islamic discourse and Neo-modernism/ Post-modernism in the perspective of Nurcholish Madjid and Abdurrahman Wahid. The Research was conducted using a qualitative approach of the type of library research. The results of this study indicate that according to these two figures Post-modernism can be used as a bridge to develop Islamic thought as a religion that will always exist in all space and time, but Islamic values must remain radiated in the modern era. Thus, as Muslims especially intellectuals must be able to balance religion and general science.